A metagenomic approach using next-generation sequencing for viral profiling of a vineyard and genetic characterization of grapevine virus E - Coetzee, Beatrix (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MSc (Genetics))--University of Stellenbosch, 2010.